2001
DOI: 10.1046/j.1442-200x.2001.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for persistence of pulmonary arterial branch stenosis in neonates and young infants

Abstract: All cases of PBS in neonates and young infants were improved. However, PBS persisted in some patients after the age of 1 year. Low birth weight and deltavelocity above 1.2 m/s are risk factors for persistent PBS. Pulmonary arterial branch stenosis was not present after the age of 1 year in 62 of 63 patients without either of these risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Pulmonary arterial branch stenosis is generally considered a transient phenomenon in neonates and young infants. It does however persist beyond a year in a minority of cases, and this persistence is related to IUGR but not prematurity 87 . IUGR, as measured by ponderal index for gestational age, is also associated with an increased incidence and severity of persistent pulmonary hypertension of the newborn 88 .…”
Section: Consequences Of Iugr For Childhood and Adult Respiratory Mormentioning
confidence: 93%
“…Pulmonary arterial branch stenosis is generally considered a transient phenomenon in neonates and young infants. It does however persist beyond a year in a minority of cases, and this persistence is related to IUGR but not prematurity 87 . IUGR, as measured by ponderal index for gestational age, is also associated with an increased incidence and severity of persistent pulmonary hypertension of the newborn 88 .…”
Section: Consequences Of Iugr For Childhood and Adult Respiratory Mormentioning
confidence: 93%
“…The published literature on the natural history of PPS includes few patients with severe PPS. [4][5][6][7][8] In the natural history study reported by Wren et al, only 7 of 35 patients had an RV pressure ≥50 mm Hg; in 5 of those 7, the RV pressure was observed to decrease spontaneously (without any interventions) by up to 40 mm Hg during the first several years of life. 6 It is possible that some of the patients in our series would have experienced similar improvements in RV pressure without intervention.…”
Section: Assessment Of Interventionmentioning
confidence: 97%
“…[1][2][3] Reports of single cases or small series have suggested that PPS may improve over time without intervention, but these studies included few patients with severe disease, which may limit their applicability to patients who are generally considered for PA intervention. [4][5][6][7][8] As with branch PA stenosis associated with other conditions, transcatheter intervention has become an accepted mode of therapy for patients with hemodynamically important PPS. Angioplasty and stent implantation have been shown to increase vessel diameter and decrease RV pressure in patients with PA stenosis in various clinical circumstances.…”
mentioning
confidence: 99%